Short-run impact of the Russian invasion of Ukraine on housing prices in Helsinki: A quantile regression analysis - Karlsson, Eemeli Erik (My University, 2023)
The housing market is closely tied to the national economy, and dwellings represent the most significant asset class for households. Thus, fluctuations in housing prices can have a significant impact on households' wealth. Prior research has found that 60% of variation of real estate return can be explained by macroeconomy. Therefore, even though housing markets must be considered regionally, macroeconomically variables plays a remarkable role. The Russian invasion of Ukraine in 2022 was a significant dramatic event that sparked widespread uncertainty and potential risks for the Finnish economy, including the housing market. Motivated by that, this thesis investigates whether the invasion affected housing prices in Helsinki by adopting a quantile regression. The benefit of quantile regression is its ability to capture the effects of explanatory variables at different points of the distribution, providing more comprehensive insights compared to traditional OLS regression. Furthermore, the study also aims to identify significant macroeconomic variables by utilizing a MIDAS regression, as this approach enables the assessment of the effects of macroeconomic variables with different frequencies on housing prices. Due to the lagged nature of the housing market and the period analyzed (January 2020-December 2022), the study primarily focuses on short-term effects. The dataset comprises 31,632 observations of housing prices collected from Hintaseurantapalvelu. The empirical results indicate that the Russian invasion of Ukraine did not have a negative impact on Helsinki housing prices, as indicated by the insignificant results in OLS and MIDAS regressions. However, the quantile regression results show a positive impact on both the lower (25th) and highest (90th) quantiles, implying a varied impact at different price levels. Further, combining results with the findings that the Economic Policy Uncertainty index lack of significance leads to the conclusion that global events and news may not have a strong influence on the Finnish housing markets. Furthermore, the short-term impact of macroeconomic variables on housing prices appears to be relatively insignificant, except for interest rates and household income, with Euribor 12-months being the most significant factor explaining house price movements.

Asuntomarkkinat ovat tiiviisti kytköksissä kansantalouteen, ja asunnot ovat kotitalouksien merkittävin varallisuusluokka. Siksi asuntojen hintavaihtelut voivat vaikuttaa merkittävästi kotitalouksien varallisuuteen. Aiemmat tutkimukset ovat osoittaneet, että 60 % kiinteistöjen reaalituottojen vaihtelusta voidaan selittää makrotaloudella. Vaikka asuntomarkkinoita onkin tarkasteltava alueellisesti, myös makrotalouden muuttujilla on merkittävä selittävä rooli. Venäjän hyökkäys Ukrainaan vuonna 2022 oli dramaattinen tapahtuma, joka aiheutti laajaa epävarmuutta ja mahdollisia riskejä Suomen taloudelle, mukaan lukien asuntomarkkinat. Tästä syystä tämä tutkielmaa tarkastelee, vaikuttiko hyökkäys todellisuudessa asuntojen hintoihin Helsingissä käyttämällä kvartiiliregressiota. Tässä tutkimuksessa menetelmän etuna on sen kyky havaita muuttujien vaikutukset eri hintatasoilla, mikä johtaa kattavimpiin tuloksiin verrattuna keskiarvomuuttujaa hyödyntävään perinteisen pienimmän neliösumman menetelmään (OLS). Hintavaikutuksen lisäksi tutkimuksessa analysoidaan merkittävät makrotaloudelliset muuttujat käyttämällä MIDAS-regressiota, joka mahdollistaa päivä-, kuukausi ja kvartaalitasolla olevien kansantalouden muuttujien vaikutusten arvioinnin asuntojen hintoihin ilman datan konsolidointia. Koska asuntomarkkinat reagoivat viiveellä markkinamuutoksiin ja analysoitava jakso on tammikuu 2020 – joulukuu 2022, keskittyy tutkimus pääasiassa lyhyen aikavälin vaikutuksiin. Aineistona käytetään Hintaseurantapalvelusta kerättyjä asuntokauppatietoja ja lopullinen otosmäärä on 31 632 havaintoa. Käyttämällä OLS- ja MIDAS-regressioita, tulokset osoittavat, että Venäjän hyökkäys Ukrainaan ei vaikuttanut negatiivisesti asuntojen hintoihin Helsingissä. Kvantiiliregressio puolestaan havaitsee varovaisen positiivisia vaikutuksia sekä alhaisimmilla (25.kvartiili) että korkeimmassa (90.kvartiili) hintaluokissa, mikä viittaa hintaluokkien erilaisiin vaikutuksiin. Kun nämä yhdistetään tuloksiin, joissa Economic Policy Uncertainty -indeksi osoittaa merkityksettömyyttä, johtopäätös on, että globaalit tapahtumat ja uutiset eivät välttämättä ole omiaan vaikuttamaan merkitsevästi Suomen asuntomarkkinoihin. Makrotaloudellisten muuttujien syvempi analyysi osoittaa lisäksi, että näiden lyhyen aikavälin vaikutukset ovat suhteellisen merkityksettömiä, lukuun ottamatta korkoja ja kotitalouksien tuloja. Kaikkein merkittävin tekijä selittämään asuntojen hintaliikkeitä valitulla ajanjaksolla on 12-kuukauden Euribor.
Keywords: asuntomarkkinat; talous; kansantalous; kvantitatiivinen analyysi; Suomi; asunnot; korko; makrotalous; housing market; macroeconomy; regressioanalyysi; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance; Finance